Ammonium ions induce inactivation of Kir2.1 potassium channels expressed in Xenopus oocytes - Shieh, R-C (Blackwell Science Inc, 2001)
1. The decay of inward currents was studied using the giant patch-clamp technique and a cloned inward rectifier K(+) channel, Kir2.1, expressed in Xenopus oocytes. 2. In inside-out patches, inward currents carried by NH(4)(+) or Tl(+) decayed over time. When the voltage was more negative, the degree and rate of decay were greater. The rate of NH(4)(+)-induced decay saturated at a symmetrical [NH(4)(+)] of ∼100 mm. The decay rate was slow (2.6 × 10(3)m(−1) s(−1)) at -140 mV with 10 mm[NH(4)(+)]. 3. Upon a 10 °C increase in temperature, the single-channel NH(4)(+) current amplitude increased by a factor of 1.57, whereas the NH(4)(+)-induced decay rate increased by a factor of 2.76. In the R148Y Kir2.1 mutant (tyrosine 148 is at the external pore mouth), NH(4)(+)-induced inactivation was no longer observed. 4. NH(4)(+) single-channel currents revealed one open and one closed state. The entry rate into the closed state was voltage dependent whereas the exit rate from the closed state was not. An increase of internal [NH(4)(+)] not only decreased the entry rate into but also elevated the exit rate from the closed state, consistent with the occupancy model modified from the foot-in-the-door model of gating. 5. These results suggest that the decay of NH(4)(+) current is unlikely to be due to a simple bimolecular reaction leading to channel block. We propose that NH(4)(+) binding to Kir2.1 channels induces a conformational change followed by channel closure. 6. The decay induced by permeant ions other than K(+) may serve as a secondary selectivity filter, such that K(+) is the preferred permeant ion for Kir2.1 channels.